2018
DOI: 10.1111/nph.15209
|View full text |Cite
|
Sign up to set email alerts
|

Constant conflict between Gypsy LTR retrotransposons and CHH methylation within a stress‐adapted mangrove genome

Abstract: The evolutionary dynamics of the conflict between transposable elements (TEs) and their host genome remain elusive. This conflict will be intense in stress-adapted plants as stress can often reactivate TEs. Mangroves reduce TE load convergently in their adaptation to intertidal environments and thus provide a unique opportunity to address the host-TE conflict and its interaction with stress adaptation. Using the mangrove Rhizophora apiculata as a model, we investigated methylation and short interfering RNA (si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 69 publications
(88 reference statements)
2
32
0
Order By: Relevance
“…This suggests that while very high TE body methylation confirms preferential suppression of the transposable elements, the dynamics of non-CG methylation at the edges of TEs must have a distinct role. A dramatic increase in CHG and CHH methylation at the boundaries of TEs has been discussed before (Li et al, 2015;Noshay et al, 2019;Wang, Liang, & Tang, 2018;Zemach et al, 2013). However, barley LTRs (borders are targeted by CHH methylation) are mostly located in heterochromatin and do not show lowered CG and CHG methylation (quite the opposite).…”
Section: Methylation Of the Transposable Elementsmentioning
confidence: 84%
“…This suggests that while very high TE body methylation confirms preferential suppression of the transposable elements, the dynamics of non-CG methylation at the edges of TEs must have a distinct role. A dramatic increase in CHG and CHH methylation at the boundaries of TEs has been discussed before (Li et al, 2015;Noshay et al, 2019;Wang, Liang, & Tang, 2018;Zemach et al, 2013). However, barley LTRs (borders are targeted by CHH methylation) are mostly located in heterochromatin and do not show lowered CG and CHG methylation (quite the opposite).…”
Section: Methylation Of the Transposable Elementsmentioning
confidence: 84%
“…Since all land plants and green algae possess the small RNA-generating RNAi machinery ( You et al, 2017 ), it is conceivable that gymnosperms, ferns and club mosses can potentially accumulate siRNAs derived from endogenous caulimovirids and/or their extant not-yet-identified episomal counterparts. Likewise, genomes of all land plants contain long terminal repeat (LTR) retrotransposons of the families Metaviridae (Ty3/Gypsy) and Pseudoviridae (Ty1/Copia) which can give rise to siRNAs as has been reported for the angiosperms A. thaliana ( Creasey et al, 2014 ; Masuta et al, 2017 ), strawberry ( Šurbanovski et al, 2016 ), mangrove ( Wang Y. et al, 2018 ), maize ( Alejandri-Ramírez et al, 2018 ) and wheat ( Sun et al, 2013 ); transposon-derived small RNAs were also reported for gymnosperms such as Picea glauca ( Liu and El-Kassaby, 2017 ) and Cryptomeria japonica ( Ujino-Ihara et al, 2018 ).…”
Section: All Families Of Land Plant Viruses and Viroids Spawn Small Rmentioning
confidence: 98%
“…However, such stressful conditions can activate transposable elements (TEs; Lyu et al , 2017). Recently, Wang et al (2018) were able to show that stress‐induced reactivations of TEs become epigenetically controlled by siRNAs‐mediated CHH methylation in the mangrove Rhizophora apiculata , but the short active windows of TEs can trigger genetic variation, possibly facilitating adaptation to new conditions.…”
Section: Epigenetic Regulation Of Plant Responses To Abiotic Conditionsmentioning
confidence: 99%